Economic value and preferences for improved biomass cookstove among rural households in selected desert frontline states in Northern Nigeria - Kabir, Ibrahim (2018)
Recently Improved Biomass Cookstove (ICS) promotion has received considerable attention in developing countries. This is primarily due to the rising adverse effects of Traditional Biomass Cookstove (TBC) usage on the one hand and benefits offered by the ICS on the other. The use of TBC in Nigeria has been widely associated with extensive environmental, socioeconomic and health related problems which to some extent, lead to chronic diseases and sometimes premature death. To address these problems, various initiatives for ICS promotion were introduced in the country. However, there is dearth of relevant information that will facilitate the success of these initiatives including the value households attached to ICS and what they like about such cooking technologies. This study estimates the economic value and preferences for ICS among households in Desert Frontline States of Northern Nigeria. This was achieved through the application of Contingent Valuation Method (CVM) and Choice Experiment (CE) - the two most widely used stated preference (SP) economic valuation techniques. Unlike existing studies, the techniques were combined for robustness purpose. Besides, this study is the first to execute both or any of these techniques on households to study ICS in Nigeria. Based on face-to-face approach, from October, 2016 to January, 2017, the study interviewed 392 rural households in desert frontline states where the wider usage of TBC is linked with substantial deforestation, desert encroachment, socioeconomic and health related problems among others.The results of CVM revealed that 74% of the surveyed households are willing to pay for ICS, with mean willingness to pay (WTP) of N66, 009.30 ($183.36) per ICS, and gender, age, income, expenses on fuelwood, cooking hours, bid price and knowledge regarding adverse effects of TBC have significant effect on households’ WTP. The result of CE revealed that the households have relatively high preferences for smoke emission reduction from cookstoves, followed by fuelwood consumption reduction, then cooking time reduction, and finally user safety. It also revealed a significant heterogeneity in the ICS preferences, with some of this variation related to the studied households’ characteristics, including income, gender, education, household size and knowledge regarding adverse effects of TBC. These study findings indicate that the surveyed rural households considerably value ICS, and have preferences for it. This signifies the possibility for implementing initiatives for ICS promotion in these areas. Based on these therefore, it is suggested that the relevant stakeholders should strengthen the implementation of initiatives for ICS promotions while taking into cognisance the households’ stated value and preferences in the design and implementation so as to achieve wider uptake.